Does Acupuncture the Day of Embryo Transfer Affect the Clinical Pregnancy Rate? Systematic Review and Meta-Analysis - Schwarze-Meza, J (SBRA - Associação Brasileira de Reprodução Assistida (Brazilian Society of Assisted Reproduction), 2018)
The effects of acupuncture on IVF outcomes is still unknown. We carried out a systematic review and meta-analysis of RCT to determine whether acupuncture performed at the time of ET improves outcomes. We searched Medline and Embase from January 1990 to June 2017, for the following terms): (acupuncture; acupuncture therapy) and (reproductive techniques, assisted; in vitro fertilization; embryo transfer). We selected RCT that compared acupuncture with sham acupuncture or no treatment. We included only trials in which acupuncture involved the insertion of needles into traditional meridian points. We evaluated the methodological quality of the trials using the Cochrane risk of bias tool. The measure of treatment effect was the pooled odds ratio of achieving a clinical pregnancy, ongoing pregnancy, or live birth for women in the acupuncture group compared with women in the control group. For pooled data, summary test statistics were calculated using the Mantel-Haenszel method, using the Rev-Man software, version 5.1. We analyzed six studies, including 2,376. In all trials, there were no significant differences between the groups concerning the mean numbers of embryos transferred, the mean age of the women undergoing the procedure, diagnose and use of ICSI. Acupuncture performed the day of ET was associated with a reduced risk of clinical pregnancy (0.87, 95% confidence interval 0.77 to 0.98). The pooled rate difference was-0.06 (-0.12 to-0.01) for clinical pregnancy. None of the trials reported significant adverse effects of acupuncture. © 2018, Sociedade Brasileira de Reproducao Assistida. All rights reserved.